RESOURCES AND TECHNOLOGY AS FACTORS AFFECTING RUSSIA’S WOOD INDUSTRY: A CASE STUDY OF THE NORTHERN REGIONS - Maxim A. Shishelov; Vladimir A. Noskov (Север и рынок: формирование экономического порядка)
The relevance of this study stems from Russia’s significant lag in the efficiency of wood use compared to leading wood-producing nations. Identifying the cause-and-effect relationships between factors and the performance of key sectors, along with determining the primary resource factors and technological factors, is crucial for developing effective measures to improve the economic performance of the industry. This study proposes a methodological toolkit for assessing the growth factors influencing the efficiency of Russia’s wood industry, employing mathematical modeling and forecasting. The findings reveal and quantify the impact of resource and technological factors on improving efficiency, providing a detailed analysis of their influence on target performance indicators. Regional assessments of resource and technological factors impacting the development of the industry were conducted. Utilizing the compiled database, resource efficiency indicators were calculated for each studied region, allowing for the identification and classification of development factors and their influence on resource productivity. The study also classifies activities in the wood industry based on the types of resource and technological factors exerting the greatest influence on the industry’s growth in the region. The proposed toolkit for assessing these factors demonstrated its effectiveness, establishing that the primary determinant of wood industry performance remains operations management. Emphasis on the integrated use of raw materials and the technological interconnection of core and auxiliary operations remains important. While innovations and high technologies are gradually increasing their contribution to economic efficiency, progress in their adoption has been slow. This underscores the need for targeted and substantive efforts to integrate advanced technologies as part of a transformative approach to production processes.